ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI HIMPUNAN DITINJAU DARI TAHAPAN NEWMAN PADA KELAS VII MTS NEGERI HAMPARAN PERAK T.A 2017/2018 - Rizky Sundari; Ella Andhany; Sajaratud Dur (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
This study aims to analyze the difficulties faced by students in solving story questions on set material in class VII MTs Negeri Hamparan Perak Academic Year 2017/2018. This research is a qualitative descriptive study. In collecting data, the methods used are observation, interview and documentation. In analyzing research data using data exposure, data reduction, and drawing conclusions. The questions used were as many as 4 problems of set stories. Subjects in the study of students of class VII-A State of Hamparan Perak State MTs, amounting to 20 students with selected respondents 3 students in the category of high, medium, and low story problem solving ability. The results showed that the three subjects made errors in transformation (transformation error), processing error (processing error), and error writing the final answer (encoding error). The factor causing this error is because the subject failed in turning the story problem into a mathematical model which results in the subject being wrong in the process of completion, writing the final answer and the existence of a careless factor.